Produksi gas hydrogen menggunakan metode elektrolisis dari elektrolit air dan air laut dengan penambahan katalis NaOH - Yoyon Wahyono; Heri Sutanto; Eko Hidayanto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
This study deals with the production of hydrogen gas (H2) using electrolysis method. H2 gas is a source of Renewable Energy (EBT).This research was conducted to determine the amount of concentration (ppm) and purity (% vol) of H2 gasses produced by electrolysis method. The purify and concentration of H2 gasses was determined using gas analyzer and MQ sensor 8 respectively. The results showed that the production of H2 gas with the highest concentration was obtained in aqueous electrolysis DM + NaCl + NaOH with a 12 volt voltage 4500 ppm. Production of H2 gas in aqua DM electrolysis, aqua DM + NaCl, and aqua DM + NaOH no detectable pollutant gas such as CO, CO2, HC, NO.Keywords: Electrolysis, Energy, Hydrogen gas, Catalyst.